2023
DOI: 10.21203/rs.3.rs-2451773/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Social vulnerability and cardiovascular risk factors in adolescents

Abstract: Background: Social vulnerability can influence in the development of cardiovascular risk factors in adolescents (CRF). For this reason, the objective of our study was to evaluate the presence of CRF in adolescents, according to social vulnerability. Methods: This is a cross-sectional study with 517 adolescents of both sexes, from 10 to 19 years of age, classified into 2 groups by social vulnerability, according to socioeconomic characteristics collected by means of questionnaires, where adolescents who did not… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 24 publications
1
1
0
2
Order By: Relevance
“…In addition, this study identified that lower education levels and lower income show a significant association with the problem. Furthermore, a study conducted in Brazil demonstrated that 65.1% of individuals reported an increase in unhealthy food intake and a decrease in the intake of fruits and vegetables among hypertensive patients [53] Moreover, the pandemic is also resulting in an increased prevalence of stress, anxiety, depression, and other mental health issues [13,15,16,38]. These findings are consistent with other studies conducted on the topic in different parts of the world [6,51].…”
Section: Discussionsupporting
confidence: 85%
“…In addition, this study identified that lower education levels and lower income show a significant association with the problem. Furthermore, a study conducted in Brazil demonstrated that 65.1% of individuals reported an increase in unhealthy food intake and a decrease in the intake of fruits and vegetables among hypertensive patients [53] Moreover, the pandemic is also resulting in an increased prevalence of stress, anxiety, depression, and other mental health issues [13,15,16,38]. These findings are consistent with other studies conducted on the topic in different parts of the world [6,51].…”
Section: Discussionsupporting
confidence: 85%
“…In addition, this study identified that lower education levels and lower income show a significant association with the problem. Furthermore, a study conducted in Brazil demonstrated that 65.1% of individuals reported an increase in unhealthy food intake and a decrease in the intake of fruits and vegetables among hypertensive patients [53].…”
Section: Plos Onementioning
confidence: 99%
“…Agora, com a segunda década dos anos 2000 encerrada e o uso das mídias digitais intrínseco no cotidiano social, nota-se uma inquietação ainda maior, agora baseada não em tendências e especulações, mas em fatos decorridos nos últimos anos. Farias, Cardoso e Nassar (2020) apontam que nos anos 1990, "[...] a internet era celebrada como uma invenção que inauguraria uma nova era da democracia cultural e política, talvez por meio de novas formas de governança eletrônica e contribuições diretas de cidadãos-jornalistas" (Farias;Nassar, 2020, p. 76). Os autores citam as análises de Curran et al (2012), que comparam as previsões a respeito do digital com as suposições feitas na década de 1950 sobre o eventual uso gratuito de eletricidade, por conta da abundância de energia nuclear.…”
unclassified
“…Embora as mídias sociais tenham facilitado e diversificado processos de difusão do conhecimento, elas oferecem um terreno fértil para a criação e propagação de desinformação (Tambuscio et al, 2015). Corroborando esse argumento, Farias, Cardoso e Nassar (2020) avaliam que "[...] as plataformas digitais não apenas introduziram novas práticas de leitura, como também mudaram os processos interpretativos que os indivíduos normalmente trazem ao ler notícias e artigos" (Farias;Nassar, 2020, p. 73).…”
unclassified